YOUNG LEARNERS WITH ATTENTION DEFICIT HYPERACTIVE DISORDER (ADHD: STRATEGY TO TEACH ENGLISH VOCABULARY - Nurul aini; Eni Prasetiyowati (STKIP PGRI Jombang, 2019)
This paper aims at analyzing teacher’s strategies in teaching vocabulary to students with ADHD as well as its implementation, the ADHD student’s responses, challenges faced by the teacher, and alternative ways to overcome it proposed by the teacher. Interview, observation, and document analysis were used to obtain the required data,. This study revealed that four strategies; attending to form, learning the meaning of word, making strong memory connection, and extending students’ vocabulary beyond the text book which were used by the teacher to teach English vocabulary to ADHD students were delivered in a chronological order. Then, seven kinds of responses; choral response, open-ended response, confusion work oriented, laughter, using native language, silence, and using L2 showed by ADHD student in the teaching learning process when the teacher used those strategies. The challenges which were faced and alternative ways which were offered by the teacher relate to symptoms of ADHD student especially his attention.